Effect of angiotensin II receptor 1 antisense oligodoexynucleotides on physiological and pathophysiological growth of cardiomyocytes - WANG Ying; WANG Jin-ming; YAN Shu-xun; LI Ming-jiang; LI Jian-jun (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the role of angiotensin II receptor 1 antisense oligodexynucleotides (AT1R-AS-ODNs) on physiological and pathophysiological growth of cardiomyocytes from normotensive rats. METHODS: Cardiomyocytes were transfected with AT1R-AS-ODNs (200 nmol/L) followed by treatment with or without angiotensin II (1 micromol/L). In situ hybridization and Western blot were used for AT1R mRNA and protein detection, respectively. c-Jun N-terminal protein kinase (JNK) activity was characterized by immune complex kinase assay. c-Jun protein expression was examined by immunocytochemistry. DNA content was detected by flow cytometric assay. Atrial natriuretic factor (ANF) expression was identified by radioimmunoassay. RESULTS: Treatment with AT1R-AS-ODNs for 24 h resulted in 51.2 % decrease in AT1R mRNA and 60.7 % in protein (P